Pengaruh Model Pembelajaran Think Pair Share Terhadap Perkembangan Keterampilan Sosial Siswa Kelas IV Pada Pembelajaran IPS - Dewi, Farah Amrillaiy; Fitra Raharja , Hawwin; Salamah, Evi Rizqi (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Background: The employment of traditional, non-interactive teaching methods frequently results in a lack of student involvement and interest in Social Studies (IPS) sessions at the primary school level. Due to the restricted use of group activities or discussions, students may lose interest in and grow bored with the course subject, which may hinder their ability to develop social skills. Thus, the objective of this paper is to investigate how the TPS cooperative model paradigm affects the social skills of IPS fourth-graders. A sample of 29 children from SDN Balongbesuk's fourth grade uses a pre-experimental design with a one group pretest-posttest design for this study. The results show that adopting the TPS cooperative learning paradigm has a considerable positive influence on the development of students' social skills. Therefore, this study comes to the conclusion that the TPS model can be a useful substitute for enhancing student involvement and social skill development in IPS sessions. The results imply that instructors should think about using this instructional technique to encourage active student involvement and improve their social skills within the IPS learning setting.